Dietary Vitamin E as a Protective Factor for Parkinson's Disease: Clinical and Experimental Evidence - Schirinzi, Tommaso; Martella, Giuseppina; Imbriani, Paola; Di Lazzaro, Giulia; Franco, Donatella; Colona, Vito Luigi; Alwardat, Mohammad; Sinibaldi Salimei, Paola; Mercuri, Nicola Biagio; Pierantozzi, Mariangela; Pisani, Antonio (Frontiers in Neurology, 2019)
Effective disease-modifying treatments are an urgent need for Parkinson’s disease (PD). A putative successful strategy is to counteract oxidative stress, not only with synthetic compounds, but also with natural agents or dietary choices. Vitamin E, in particular, is a powerful antioxidant, commonly found in vegetables and other components of the diet. In this work, we performed a questionnaire based case-control study on 100 PD patients and 100 healthy controls. The analysis showed that a higher dietary intake of Vitamin E was inversely associated with PD occurrence independently from age and gender (OR = 1.022; 95% CI = 0.999 – 1.045; p<0.05), though unrelated to clinical severity. Then, in order to provide a mechanistic explanation for such observation, we tested the effects of Vitamin E and other alimentary antioxidants in vitro, by utilizing the homozygous PTEN-induced kinase 1 knockout (PINK1−/−) mouse model of PD. PINK1−/− mice exhibit peculiar alterations of synaptic plasticity at corticostriatal synapses, consisting in the loss of both long-term potentiation (LTP) and long-term depression (LTD), in the absence of overt neurodegeneration. Chronic administration of Vitamin E (alpha-tocopherol and the water-soluble analogue trolox) fully restored corticostriatal synaptic plasticity in PINK1−/− mice, suggestive of a specific protective action. Vitamin E might indeed compensate PINK1 haploinsufficiency and mitochondrial impairment, reverting some central steps of the pathogenic process. Altogether, both clinical and experimental findings suggest that Vitamin E could be a potential, useful agent for PD patients. These data, although preliminary, may encourage future confirmatory trials.